PEMBINAAN KARAKTER MUJA ̅HADAH DAN ISTIQO ̅MAH DALAM PROGRAM TAHFIDZ AL-QUR’AN DI SD PLUS NURUL AULIA KOTA CIMAHI - Anisa Indah Sabila; Bambang Saiful Ma’arif; Ayi Sobarna (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2025)
Character education is fundamental in facing modern challenges. The characters of mujāhadah (sincerity) and istiqōmah (consistency) are the keys to developing a resilient personality. However, initial observations indicate a lack of discipline among some students in the tahfidz program, such as lateness, lack of seriousness in participating in Al-Qur'an memorization activities, and the use of impolite language. This study aims to describe the character development process, analyze the implementation, identify the formed characters, and analyze the supporting and inhibiting factors for the development of mujāhadah and istiqōmah in the Al-Qur'an memorization program at SD Plus Nurul Aulia, Cimahi City. The research method used is descriptive qualitative, with triangulation data collection techniques (interviews, observation, and documentation) and informant selection using purposive sampling. The results show that SD Plus Nurul Aulia implements the tahfidz program with a unique and comprehensive approach, supported by strategic planning, detailed routine implementation, and comprehensive evaluation. This program has succeeded in creating significant improvements in student discipline, responsibility, and religiosity. With the support of a conducive environment and the active role of parents, despite facing external obstacles, they can be proactively overcome.